Augmented Reduced-Intensity Regimen Does Not Improve Postallogeneic Transplant Outcomes in Acute Myeloid Leukemia. Issue 7 (1st March 2021) - Craddock, Charles; Jackson, Aimee; Loke, Justin; Siddique, Shamyla; Hodgkinson, Andrea; Mason, John; Andrew, Georgia; Nagra, Sandeep; Malladi, Ram; Peniket, Andrew; Gilleece, Maria; Salim, Rahuman; et al.
Abstract : PURPOSE: Reduced-intensity conditioning (RIC) regimens have extended the curative potential of allogeneic stem-cell transplantation to older adults with high-risk acute myeloid leukemia (AML) and myelodysplasia (MDS) but are associated with a high risk of disease relapse. Strategies to reduce recurrence are urgently required. Registry data have demonstrated improved outcomes using a sequential transplant regimen, fludarabine/amsacrine/cytarabine-busulphan (FLAMSA-Bu), but the impact of this intensified conditioning regimen has not been studied in randomized trials. PATIENTS AND METHODS: Two hundred forty-four patients (median age, 59 years) with high-risk AML (n = 164) or MDS (n = 80) were randomly assigned 1:1 to a fludarabine-based RIC regimen or FLAMSA-Bu. Pretransplant measurable residual disease (MRD) was monitored by flow cytometry (MFC-MRD) and correlated with outcome. RESULTS: There was no difference in 2-year overall survival (hazard ratio 1.05 [85% CI, 0.80 to 1.38] P = .81) or cumulative incidence of relapse (CIR) (hazard ratio 0.94 [95%CI, 0.60 to 1.46] P = .81) between the control and FLAMSA-Bu arms. Detectable pretransplant MFC-MRD was associated with an increased CIR (2-year CIR 41.0% v 20.0%, P = .01) in the overall trial cohort with a comparable prognostic impact when measured by an unsupervised analysis approach. There was no evidence of interaction between MRD status and conditioning regimen intensity for relapse or survival. Acquisition of full donor T-cell chimerism at 3 months abrogated the adverse impact of pretransplant MRD on CIR and overall survival. CONCLUSION: The intensified RIC conditioning regimen, FLAMSA-Bu, did not improve outcomes in adults transplanted for high-risk AML or MDS regardless of pretransplant MRD status. Our data instead support the exploration of interventions with the ability to accelerate acquisition of full donor T-cell chimerism as a tractable strategy to improve outcomes in patients allografted for AML.